2017
DOI: 10.1108/ijcthr-10-2016-0102
|View full text |Cite
|
Sign up to set email alerts
|

Sexualisation and harassment in hospitality workplaces: who is responsible?

Abstract: Purpose This paper aims to examine employee responses to sexual behaviour in hospitality workplaces, to determine their roles and responsibilities in harassment prevention. Design Female workers in restaurants and bars were recruited using the snowball technique, and data collected through 18 interviews. An interpretivist approach was used to guide the data collection and analysis. Findings The study found that harassment coping strategies developed with age and experience rather than through training, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
6
29
0
Order By: Relevance
“…However, unlike other studies, the participants in this study emphasized that some women and agents (brokers) were also responsible for the act. This nding supports the statement that emphasizes the more considerable in uence of peers than management on labor sexualization [50].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, unlike other studies, the participants in this study emphasized that some women and agents (brokers) were also responsible for the act. This nding supports the statement that emphasizes the more considerable in uence of peers than management on labor sexualization [50].…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with other studies [19,[63][64][65][66], the participants in this study experienced work-related effects, health-related effects (i.e., mental and behavioral health, physical health, and reproductive health) [67], economic effects [68], and family undermining [21,69]. Previous studies of SH in hospitality workplaces revealed the peculiarities of the industry such as customer power [10,50,70], the sexualization of the workplaces [18,62], workplace culture [71], and sociodemographic characteristics [72] of women as risk factors of SH. Other studies also uncover that the peculiarities mentioned above might end in different work-related consequences [6,73].…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with other studies [23,[61][62][63][64], the participants in this study experienced work-related effects, health-related effects (i.e., mental and behavioral health, physical health, and reproductive health) [65], economic effects [66], and family undermining [24,67]. The possible reasons might be the peculiarities of the industry, such as customer power [14,49,68], the sexualization of the workplaces [22,60], workplace culture [69], and sociodemographic characteristics [70] of women as risk factors of SH. Consequently, the peculiarities mentioned above might end in different work-related consequences [13,71].…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, unlike other studies, the study participants emphasized that some women and agents (brokers) were also responsible for the act. This nding supports the statement that emphasizes peers' more considerable in uence than management on labor sexualization [49]. This covert and overt involvement of hospitality workplace managers and co-workers/peers, and agents (brokers) in the perpetration act made the problem further complicated.…”
Section: Discussionsupporting
confidence: 79%
“…As Poulston (2008a), Azlan and Kozak (2012) and others suggested, hospitality provision may infer an asymmetric power relationship between the paying consumer and the staff who are there to meet their needs. Studies have also suggested that uniform policies may exacerbate the problems (Waudby & Poulston, 2017). For example, name badges allow customers to know and address staff by their first names.…”
Section: Organisational Antecedents and Driversmentioning
confidence: 99%